Shading decreases lodging resistance of wheat under different planting densities by altering lignin monomer composition of stems - Luo, Yongli; Chang, Yonglan; Li, Chunhui; Wang, Yuanyuan; Cui, Haixing; Jin, Min; Wang, Zhenlin; Li, Yong (Frontiers in Plant Science, 2022)
To clarify the influences of shading stress and planting density on the lignin monomer composition of wheat stems and their relationship with lodging resistance, Lodging resistant variety Shannong 23 (SN23) and lodging sensitive variety Shannong 16 (SN16) were grown during 2018‒2019 and 2019‒2020 growing seasons. The planting densities were 150 × 104 plants ha-1 (D1), 225 × 104 plants ha-1 (D2) and 300 × 104 plants ha-1 (D3). At the jointing stage, an artificial shading shed was used to simulate shading stress. Then the effects of shading on stem morphological characteristics, lignin monomer composition and lodging resistance of wheat under different planting densities were studied. Results indicate that shading at the jointing stage increased the length of basal internodes and the plant height and moved the height of center of gravity (CG) upward. Moreover, the stem diameter and the wall thickness decreased by 0.10‒0.53 mm and 0.18‒0.40 mm, respectively. The stem filling degree was reduced accordingly. As indicated by the correlation analysis and the stepwise regression analysis, shading-induced lodging mainly resulted from changes in the stem morphological characteristics and lignin accumulation. The influential magnitude of these factors was ordered as follows: stem filling degree, wall thickness, lignin content, contents and proportions of monomers S and H, and length of the second internode. The expression abundance of TaPAL, TaCOMT, TaCCR, and TaCAD declined in response to shading stress and high planting density. As a result, the distribution ratios of photosynthetic carbon sources to lignin monomers S, G and H were changed. The lignin content of stems on the day 42 after the jointing stage decreased by 18.48%. The monomer S content decreased, while the content and proportion of monomer H increased, thus weakening the breaking strength of wheat stems.